Relapse among drug addicts in East Coast Malaysia: a qualitative study of risk factors - Che Amat, Muhammad Asyraf; Ahmad, Jamaludin; Jailani, Othman; Wan Jaafar, Wan Marzuki; Zaremohzzabieh, Zeinab (Human Resource Management Academic Research Society, 2020)
This study aimed to identify the risk factors of relapse among drug addicts who were repeatedly admitted to the Narcotics Recovery and Addiction Centre (PUSPEN). This qualitative study utilized an interview method to gain a deeper understanding of the factors that contribute to the relapse phenomenon. The study sample comprised of seven relapsed drug addicts who were admitted to the centre more than once. The interview sessions were conducted at two PUSPEN centers in the east coast of Malaysia, which are PUSPEN Jeli and Bachok. These centers cater for both male and female drug addicts. The current study found that the risk factors of relapse among the drug addicts are internal factors. The themes that emerged in these risk factors include lack of willpower, boredom, frustration, lack of religious knowledge and practices, anger, and resentment. Apart from that, other risk factors are such as lack of family support, income factor (scarce income and surplus income), the influence from old friends, rejection from the community, social media influence, and no place to go after being released are also contributing factors to the reoccurrence of relapse. The findings of this study provide practical implications for the drug treatment and rehabilitation in Malaysia.